86.88 kilometers is 53.98 miles
Answer:
( -
,
)
Step-by-step explanation:
Given the 2 equations
9x + 8y = 3 → (1)
6x - 12y = - 11 → (2)
To eliminate the y- term multiply (1) by 1.5
13.5x + 12y = 4.5 → (3)
Add (2) and (3) term by term
(6x + 13.5x) + (- 12y + 12y) = (- 11 + 4.5)
19.5x = - 6.5 ( divide both sides by 19.5 )
x =
= - ![\frac{1}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7D)
Substitute this value into either of the 2 equations and solve for y
Using (1), then
- 3 + 8y = 3 ( add 3 to both sides )
8y = 6 ( divide both sides by 8 )
y =
= ![\frac{3}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B4%7D)
Solution is (-
,
)
X
X+2
X+4
Those are 3 consecutive odd integers
Your answer would be B and C